The association between emotional arousal and color lightness of facial digital expressions of social robots - Chengxing, Xu; Ying, Fu; Aonini, Ren; Qiong, Wang (Frontiers in Psychology, 2026)
In human–robot social interactions, a robot’s facial expressions serve as a crucial channel for conveying emotions and fostering trust. However, current social robots predominantly employ emoji-like icons and simulated muscle movements for anthropomorphic ex-pression, and research on facial color–emotion relationships tends to adjust hue, saturation, and lightness simultaneously—overlooking how color lightness alone influences emotional intensity. This study explores the specific link between emotion type and color lightness in social robots’ digital facial expressions to enhance affective communication in human–computer interaction. In our experiment, participants viewed robot faces dis-playing the same emotion at varying lightness levels and rated perceived arousal on a 1–5 scale. The results confirm that manipulating color lightness significantly modulates emotional arousal. Overall, these findings suggest that adaptive lightness adjustments in robot facial colors can yield more realistic and intuitive affective interactions between humans and machines.